The Hematoma Block versus Hematoma Plus Wrist Nerve Block in the Reduction of Distal Radius Fractures - Jiménez, Isidro; Aniel-Quiroga Bilbao, Manuel; Monge-Baeza, Alejandro; Fruner, Giovanni; García-Toledo, Alba; Liñán-Padilla, Alejandro (Journal of Wrist Surgery, 2024)
Distal radius fractures are extremely common. Most of them can be treated conservatively, but there are still many controversies about this nonoperative treatment. The purpose of this study was to assess whether the pain experienced during distal radius fracture reduction using the hematoma block plus a nerve block at the wrist is less than the perceived pain using an isolated hematoma block and whether the success of the closed reduction remains at least the same.A total of 192 patients were included in a comparative study to assess whether the pain experienced during wrist fracture reduction using the hematoma block plus a nerve block at the wrist was less than using an isolated hematoma block and whether they were equally effective.The mean Visual Analog Scale (VAS) for pain at the wrist was 4.6 in the hematoma plus nerve block and 5.1 in the isolated hematoma block. The score at the fingers was 5.2 in the hematoma plus nerve block and 7.3 in the hematoma block. The success of the procedure was the same among groups.The hematoma plus nerve block is more effective than the isolated hematoma block in reducing the pain during wrist fracture reduction, especially for fingers pain. The mean VAS was far from ideal and further focused research can be very useful because of the great clinical impact it can have.Therapeutic study. Prospective cohort study—Level II.
Keywords: block; distal radius; hematoma; pain; reduction; wrist